Peran Kecerdasan Emosional dan Karakteristik Individuterhadap Stres Pada Individu Dewasa Awal Yang Mengalami Putus Cinta - Fairus Hafizhah, Nadia; Pradna Paramita, Pramesti (Jurnal Syntax Fusion, 2023)
The study aimed to determine the role between emotional intelligence and demographic factors on stress in early adult who experience breakups. The breakup experience that happens in early adult may causes psychological problems such as stress. However, psychological problems such as stress due to breakups may be perceived differently among individuals. Emotional intelligence is an individual ability to be able to recognize, to accept, and to recognize the emotions of themselves and others, which is considered to be related to stress. Participants in this study were 135 female/male subjects who had breakup experience, and aged 18 to 40. The method used a quantitative research survey, where participants were asked to complete The Practical EQ Emotional Intelligence Self-Assessment, Perceived Stress Scale, and demographic factors questionnaire. The analysis used a simple linear regression test by using the IBM SPSS 25.00 for Windows statistical program. The result indicated a significant role between self-awareness dan self-control dimension of emotional intelligence with reduce stress level with significant value 0,00 (p<0,05), however all dimension of emotional intelligence simultaneously plays a role 44,1% on stress levels Meanwhile, the variables of individual characteristic are not significantly correlated so that regression analysis is not carried out.